2005
DOI: 10.1097/01.all.0000191240.28255.ab
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of pollen allergens: recommendations for immunotherapy vaccines

Abstract: Characterization of specific pollen allergens and their protein families has provided insight into the grounds for cross-reactivity. Continuing clarification of these relationships will allow the substitution and consolidation of inhalant extracts as described in the conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 64 publications
(67 reference statements)
4
15
0
Order By: Relevance
“…There is ample evidence that both group 1 and group 5 allergens are well conserved among Pooideae, with an amino acid sequence homology in the range of 90 and 55–80%, respectively [13,14,15]. There is some level of conservation of other pollen allergens besides groups 1 and 5 among Pooideae, with homologies at the amino acid level ranging from 40 to 60% (i.e.…”
Section: Arguments In Favour Of a Mixed-pollen Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence that both group 1 and group 5 allergens are well conserved among Pooideae, with an amino acid sequence homology in the range of 90 and 55–80%, respectively [13,14,15]. There is some level of conservation of other pollen allergens besides groups 1 and 5 among Pooideae, with homologies at the amino acid level ranging from 40 to 60% (i.e.…”
Section: Arguments In Favour Of a Mixed-pollen Vaccinementioning
confidence: 99%
“…Besides its broad historical utilisation for desensitisation purposes by clinicians, the 5 grass combination can be justified based on (1) the widespread distribution in Europe and North America of these Pooideae, which belong to 2 distinct tribes; (2) a well-characterised content of both major and minor allergens [3, 5,10,11,12,13,14,15]. …”
Section: Which Mixture Of Pooideae Grasses Should We Use?mentioning
confidence: 99%
“…IgE antibody or T-cell receptor, cross-reacting with similar affinity to homologous allergens from different species [1,2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…5). According to previous data, the major antigens in pine pollen are of 42 and 6-8 kDa (Weber 2005). In addition, in the case of Pinus radiata, it has been reported that the main allergens are of 140,85,70,55,42,32,22,19, and 6-8 kDa (Cornford et al 1988;Gastaminza et al 2009).…”
Section: Analysis Of Pine Pollen Proteinmentioning
confidence: 93%